Analysis of the implementation of an assistance proposal in school-hospital from a nursing manager perspective - dos Santos Lima, Isis Fernanda; Melleiro, Marta Maria (O Mundo da Saúde, 2006)
The research aimed to understand the nursing controlling perception in the implantation of an assistance proposal, aiming at the adhesion to the Child-Friend Hospital Initiative (IHAC). It was a qualitative research carried through in the Division of Maternal- Infantile Nursing of USP’s University Hospital (HU-USP), with the participation of five managers. Data collection was carried through interviews and narratives were analyzed according to Janesick perspective. Seven categories were extracted from narratives, and they were interpreted according to authors who investigate the subject. The results of the present study, such as the necessity of changes in the unit structure and the revision of the work process, present data for the evaluation and reformulation necessary to the implantation of IHAC in the HU-USP, favoring this way its qualification as a Child-Friend Hospital.